2016
DOI: 10.1007/s11255-016-1436-3
|View full text |Cite
|
Sign up to set email alerts
|

A critical appraisal of chronic kidney disease mineral and bone disorders clinical practice guidelines using the AGREE II instrument

Abstract: Most guidelines assessing CKD-MBD suffer from serious shortcomings using AGREE criteria although limitations with respect to AGREE criteria do not necessarily lead to inappropriate recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 45 publications
3
31
0
Order By: Relevance
“…A similar situation was reported by Armstrong et al in a recent appraisal of osteoporosis guidelines, with domain 6 presenting with the lowest score (45%) [ 23 ]. The score of this domain was low in several other studies [ 24 , 25 , 27 , 28 ], with few exceptions [ 26 ]. Regarding “Editorial Independence” evaluation, the AGREE II considers two items related to funding bodies or potential authors’ competing interests that may have influenced the guideline content [ 19 ].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…A similar situation was reported by Armstrong et al in a recent appraisal of osteoporosis guidelines, with domain 6 presenting with the lowest score (45%) [ 23 ]. The score of this domain was low in several other studies [ 24 , 25 , 27 , 28 ], with few exceptions [ 26 ]. Regarding “Editorial Independence” evaluation, the AGREE II considers two items related to funding bodies or potential authors’ competing interests that may have influenced the guideline content [ 19 ].…”
Section: Discussionmentioning
confidence: 88%
“…In addition, the total score (expressed as mean ± standard deviation, SD) of guidelines and domains was calculated. Domain scores were categorised as good (≥ 80%), acceptable (60–79,9%), low (40–59,9%), or very low (<40%), similar to a previous similar paper [ 24 ]. Data extraction, collection, and scoring were done by a fifth independent reviewer (LMS) with 14 years of experience in musculoskeletal US and scientific research, using a Microsoft Excel® 2016 spreadsheet.…”
Section: Methodsmentioning
confidence: 99%
“…Armstrong et al reported similar results (45%) after conducting an evaluation of osteoporosis guidelines focusing on physical activity and safe movement [18]. This domain scored low in several other studies [19, 20, 22, 23], with few exceptions [21]. According to AGREE II, the evaluation of “editorial independence” considers two aspects related to funding bodies or potential authors’ competing interests that may influence the guideline content.…”
Section: Discussionmentioning
confidence: 95%
“…In particular, AGREE II does not evaluate the degree of consistency between the guideline recommendations and the reported evidence [19]. Also, AGREE II does not specifically evaluate the clinical content, a limitation that is common to several appraisal tools [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation